Why human nature matters between biology and politics - Mameli, Matteo (Bloomsbury Academic, 2024)
Does human nature constrain social and political change, or do social and political changes transform human nature? Why Human Nature Matters argues that the answer to both questions is 'yes'. This philosophical account offers new tools for connecting biological and political perspectives on humanity. The focus is on the construction of human relations and environments, and on the complex materiality of these transformations. The structure and history of the philosophical and scientific debates on human nature show that political praxis and ideas about human nature interact in a variety of ways. Ideas about human nature affect how people live their lives, organize their societies, and imagine their futures. The book explores these processes and their implications for the present state of our species. Appeals to human nature can uphold the status quo or advocate for change, and they can be wielded for exclusion or inclusion. The book proposes ways of thinking about human nature that stress the importance of diversity, plasticity, cooperation, and freedom.